Immune Cell Paracrine Signaling Drives the Neutrophil Response to A. fumigatus in an Infection-on-a-Chip Model - Hind, Laurel E. (Cell Mol Bioeng, 2020)
INTRODUCTION: Neutrophils act as first responders during an infection, following signals from the pathogen as well as other host cells to migrate from blood vessels to the site of infection. This tightly regulated process is critical for pathogen clearance and, in many cases, eliminates the pathogen without the need for an additional immune response. It is, therefore, critical to understand what signals drive neutrophil migration to infection in a physiologically relevant environment. METHODS: In this study, we used an infection-on-a-chip model to recapitulate many important aspects of the infectious microenvironment including an endothelial blood vessel, an extracellular matrix, and the environmental fungal pathogen Aspergillus fumigatus. We then used this model to visualize the innate immune response to fungal infection. RESULTS: We found that A. fumigatus germination dynamics are influenced by the presence of an endothelial lumen. Furthermore, we demonstrated that neutrophils are recruited to and swarm around A. fumigatus hyphae and that the presence of monocytes significantly increases the neutrophil response to A. fumigatus. Using secreted protein analysis and blocking antibodies, we found that this increased migration is likely due to signaling by MIP-1 family proteins. Finally, we demonstrated that signal relay between neutrophils, mediated by LTB4 signaling, is also important for sustained neutrophil migration and swarming in response to A. fumigatus infection in our system. CONCLUSIONS: Taken together, these results suggest that paracrine signaling from both monocytes and neutrophils plays an important role in driving the neutrophil response to A. fumigatus. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12195-020-00655-8) contains supplementary material, which is available to authorized users.